2004
DOI: 10.1007/s00702-004-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar disorder, schizophrenia, and other psychotic disorders in adults with childhood onset AD/HD and/or autism spectrum disorders

Abstract: Individuals with attention-deficit/hyperactivity disorder (AD/HD) and autism spectrum disorders (ASD) often display symptoms from other diagnostic categories. Exclusion criteria in the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) and the International Statistical Classification of Diseases and Related Health Problems (ICD-10) impede the use of categorical diagnoses to describe the particular problem constellation in a patient. In this study, we describe the prevalence and patterns of comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
140
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(158 citation statements)
references
References 17 publications
10
140
2
6
Order By: Relevance
“…This review has highlighted the need for large-scale epidemiological studies in order to establish accurate rates of co-occurrence of the two disorders, and revision of diagnostic criteria may be required in order to facilitate recognition of their co-occurrence (Davidson et al, 2014;Stahlberg et al, 2004). Discrepancy between ASD identification pre-and-post research studies highlights the need for better screening and identification of ALTs in individuals presenting with psychotic symptoms, however further research is required in order to enhance understanding of the overlapping and distinguishing features of ASD and psychosis in order to facilitate differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This review has highlighted the need for large-scale epidemiological studies in order to establish accurate rates of co-occurrence of the two disorders, and revision of diagnostic criteria may be required in order to facilitate recognition of their co-occurrence (Davidson et al, 2014;Stahlberg et al, 2004). Discrepancy between ASD identification pre-and-post research studies highlights the need for better screening and identification of ALTs in individuals presenting with psychotic symptoms, however further research is required in order to enhance understanding of the overlapping and distinguishing features of ASD and psychosis in order to facilitate differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have also described the occurrence of depression and other mood disorders in persons with Asperger syndrome, especially in adolescence (Ghaziuddin et al, 1998). In a more recent study, Gillberg and colleagues found that out of a sample subjects with autism spectrum disorders, including those with AS, 7% had bipolar disorder with psychotic features and 7.8% had schizophrenia and other psychotic disorders (Stahlberg, Soderstrom, Rastam, & Gillberg 2004). The present study extends these findings to the parents, and suggests that parents of subjects with AS also appear to be at an increased risk of mood disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of genetic overlap reveals numerous correlations among disorders, many of which are well established (e.g., see refs. [3][4][5][6][7][8], whereas other correlations appear previously undescribed.…”
Section: /59mentioning
confidence: 99%